A library-publisher partnership for open access - Monica Ward; Joanie Lavoie (Liber Quarterly: The Journal of European Research Libraries, 2021)
This article presents an overview of a strategic partnership undertaken by the Canadian Research Knowledge Network (CRKN) and the Érudit Consortium (Érudit) to support the move towards open access for Canadian francophone scholarly journals.